Qiraat Varieties as Language Games from Ludwig Wittgenstein's Perspective - Heri Iswandi; Maryono; Abdul Matin Bin Salma (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the variant readings (qira’at) of the Qur’an through the language games approach proposed by Ludwig Wittgenstein. In the Islamic scholarly tradition, qira’at are commonly understood as variations in recitation transmitted from the Prophet Muhammad and authenticated through chains of transmission (sanad). However, this study offers a different perspective by viewing qira’at as linguistic practices embedded within specific social, historical, and theological contexts. By employing a qualitative method and a philosophy of language approach, this research finds that the diversity of qira’at reflects a plurality of language games, each with its own rules, functions, and contexts of use. This suggests that meaning in the Qur’an is neither singular nor static, but rather dynamic and shaped by its practical usage.